Management of Cutaneous Wounds with Herbal Essential Oils - Linda Julianti Wijayadi; Kelvin Kelvin; Evan Dionesia Gravianto; Fransisca Nathalia Cindy Kartawijaya (GLOBAL HEALTH SCIENCE GROUP, 2024)
In order to improve the effectiveness of cutaneous wound healing, various efforts have been made. Multiresistant bacteria are one of the challenges of wound healing treatment. Herbal essential oil is one of the alternatives that can be used, because of its broad-spectrum antimicrobial effects. The purpose of this literature review is to discuss in more depth the role of herbal essential oils in wound healing. Articles were retrieved from several databases such as Google Scholar, Sciencedirect, Cochrane, and Pubmed. Articles were searched using predetermined keywords, which were then screened from 2014-2024, resulting in 11 articles that met the inclusion criteria. The herbal essential oils discussed, namely immortelle essential oil, lavender essential oil, tea tree essential oil, chamomile essential oil, calendula essential oil, and castor essential oil, have been shown to be significantly beneficial in wound healing in studies on mice. The herbal essential oils are expected to be an alternative treatment in wound healing, especially in humans.